Postoperative uvular necrosis: A case series and literature review. (30th May 2019) - Reid, Jonathan W.; Samy, Arjun; Jeremic, Goran; Brookes, Jonathan; Sowerby, Leigh J.
Abstract : Objectives/Hypothesis: Postoperative uvular necrosis is rare, but can be distressing to the patient when it unexpectedly occurs. Little has been published regarding its predisposing factors and pathophysiology. The purpose of this comprehensive review was to compile cases of postoperative uvular necrosis and identify risk factors and potential causes for this complication. Study Design: Retrospective case series. Methods: The study was performed at an academic tertiary care referral center. Clinical records from four patients treated for postoperative uvular necrosis from 2008 to 2018 were reviewed. A comprehensive literature review was also performed. The MEDLINE, Embase, and Scopus databases were searched, as well as the grey literature. All case reports and literature reviews in the English literature from 1978 to 2018 were systematically identified for review. Results: Four cases of postoperative uvular necrosis diagnosed clinically at our institution were included. The comprehensive literature review identified 26 reports and seven case series, totaling 53 cases of this complication. Use of suction was reported in 19 cases, and six cases reported no use of suction. Ninety‐four percent of cases were treated conservatively, whereas 6% underwent excision. Ninety‐one percent resolved within 14 days. Conclusions: Impingement with various devices and vascular trauma from suction each likely play a role in postoperative uvular necrosis. Male oropharyngeal anatomy may be a risk factor, but neither the type of instrumentation nor the type of procedure seem to predict this complication. Proper positioning of the patient and instruments and minimizing suction force help prevent uvular injury. Level of Evidence: NA Laryngoscope, 130:880–885, 2020